On the practical applicability of thermal evaporation technique to fabricate Na thin metal anodes for Na-metal batteries - L. Fallarino; G. Salaverri; R. Cid; E. Gucciardi; M. Cabello; E. Gonzalo; M. Galceran (Journal of Power Sources Advances, 2024)
We demonstrate, as proof of concept, a materials design path that allows us to exploit thermal deposition technique to fabricate sodium (Na) metal anodes at the microscale. Our study reveals that Na thin anodes <10 μm, directly coated on a stainless-steel current collector, reduces the energy barrier of Na nucleation during plating process. Likewise, evaporated thin-film sodium anodes enable achieving a cycling in a full battery configuration as stable as with bulk Na anode, and considerably more stable than the here presented anode-less case. These insights may lead to practical design changes toward the efficient use of metallic Na, alleviating weight and costs. In addition, they provide a solid starting point for future developments that focus on improving the stability and extending the life of Na-metal batteries. All this paves the way for the next-generation of sodium-based energy storage technologies, where energy density and cost are key factors.